Administration of dehydroepiandrosterone (DHEA) enhances visual-spatial performance in postmenopausal women - Stangl, Bethany; Hirshman, Elliot; Verbalis, Joseph (Behavioral neuroscience, 2011)
The current article examines the effect of administering dehydroepiandrosterone (DHEA) on visual-spatial performance in postmenopausal women (N = 24, ages 55-80). The concurrent reduction of serum DHEA levels and visual-spatial performance in this population, coupled with the documented effects of DHEA's androgenic metabolites on visual-spatial performance, suggests that DHEA administration may enhance visual-spatial performance. The current experiment used a double-blind, placebo-controlled crossover design in which 50 mg of oral DHEA was administered daily in the drug condition to explore this hypothesis. Performance on the Mental Rotation, Subject-Ordered Pointing, Fragmented Picture Identification, Perceptual Identification, Same-Different Judgment, and Visual Search tasks and serum levels of DHEA, DHEAS, testosterone, estrone, and cortisol were measured in the DHEA and placebo conditions. In contrast to prior experiments using the current methodology that did not demonstrate effects of DHEA administration on episodic and short-term memory tasks, the current experiment demonstrated large beneficial effects of DHEA administration on Mental Rotation, Subject-Ordered Pointing, Fragmented Picture Identification, Perceptual Identification, and Same-Different Judgment. Moreover, DHEA administration enhanced serum levels of DHEA, DHEAS, testosterone, and estrone, and regression analyses demonstrated that levels of DHEA and its metabolites were positively related to cognitive performance on the visual-spatial tasks in the DHEA condition.